Effect of 10 week beta-alanine supplementation on competition and training performance in elite swimmers - Chung, W.; Shaw, G.; Anderson, M. E.; Pyne, D. B.; Saunders, P. U.; Bishop, D.; Burke, L. (Nutrients, 2012)
Although some laboratory-based studies show an ergogenic effect with beta-alanine supplementation, there is a lack of field-based research in training and competition settings. Elite/Sub-elite swimmers (n = 23 males and 18 females, age = 21.7 ± 2.8 years; mean ± SD) were supplemented with either beta-alanine (4 weeks loading phase of 4.8 g/day and 3.2 g/day thereafter) or placebo for 10 weeks. Competition performance times were log-transformed, then evaluated before (National Championships) and after (international or national selection meet) supplementation. Swimmers also completed three standardized training sets at baseline, 4 and 10 weeks of supplementation. Capillary blood was analyzed for pH, bicarbonate and lactate concentration in both competition and training. There was an unclear effect (0.4%; ±0.8%, mean, ±90% confidence limits) of beta-alanine on competition performance compared to placebo with no meaningful changes in blood chemistry. While there was a transient improvement on training performance after 4 weeks with beta-alanine (-1.3%; ±1.0%), there was an unclear effect at ten weeks (-0.2%; ±1.5%) and no meaningful changes in blood chemistry. Beta-alanine supplementation appears to have minimal effect on swimming performance in non-laboratory controlled real-world training and competition settings.